Pemanfaatan Teknologi Papan Digital dalam Menstimulasi Kemampuan Numerasi Anak Usia 5-6 Tahun - Suci Putri Rachmawati; Kristiana Maryani; Atin Fatimah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Early childhood numeracy skills need to be optimally stimulated, but learning that is still dominated by conventional methods often fails to facilitate a concrete and engaging understanding of mathematical concepts. This study aims to describe the implementation, evaluation, and challenges of utilizing digital board technology to stimulate the numeracy skills of children aged 5–6 years at Putra II Serang Kindergarten. The study used a descriptive qualitative approach with educators and group B students as subjects. Data were collected through passive participant observation, in-depth interviews, and documentation. Data validity was obtained through triangulation of sources and techniques, extended observations, persistent observations, and member checking. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the use of digital boards was implemented systematically through the planning, implementation, and evaluation stages. Teachers utilized touchscreen features, multimedia, and educational games to introduce the concepts of number, quantity, simple arithmetic operations, shapes, patterns, and sequences. Interactive learning was able to increase enthusiasm, active participation, and children's understanding of numeracy. However, its implementation still faces obstacles such as limited facilities, teacher readiness, and the need to develop more varied learning content.